(untitled) (Journal of Parents and Teachers, 2016)
Schools as learning communities invite us to think about a school that bases its actions on scientific evidence, pursuing academic success of all students and promoting social cohesion. A school that goes beyond the walls of the school itself, and is able to transform the reality in which it is included. In short, they open the doors to a community that dreams the best education for all students, and that makes this dream possible from the implementation of successful educational actions.